Effects of bin proximity and informational prompts on recycling and contamination - Rosenthal, Sonny (2022)
This between-subjects experiment manipulated the proximity of a waste bin relative to a recycling bin and the presence of information about why and how to rinse recyclables. After completing a yogurt taste test, 272 undergraduate students disposed of their plastic tasting cups in either a waste bin or a recycling bin. Binary logistic regression showed use of the recycling bin roughly tripled when the waste bin was made less convenient by moving it away from the tasting area (p <. 001, Nagelkerke R2 = 0.54). Univariate ANOVA showed the contamination level of recycled items was lower when an informational prompt indicated how clean recyclables need to be (p <. 001, η2p = 0.08), but not when it indicated why rinsing is important. These findings showcase how manipulating the physical environment can be a powerful tool to steer behavior and how tailored information can complement physical changes to promote proenvironmental actions.